Sustainable Development 2030: Primary School Education Policy based on Multicultural Education - Sari, Erika; Marfilinda, Riri; Noor, Ady Ferdian (International Journal of Universal Education, 2024)
The global education development agenda is reflected in Goal 4 (SDG4) of the 2030 Sustainable Development Agenda, which was adopted by countries around the world, including Indonesia. Indonesia strives to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all by 2030 through various government policies. The policy aims to reconfigure the entire education system to support and encourage curriculum and learning, so that all critical targets and goals (SDGs) of the 2030 agenda for sustainable development can be achieved.The education system in Indonesia is derived from Indonesian culture and society. This is what differentiates the system in Indonesia from other countries, we are different from the United States, Australia, different from neighboring countries such as Malaysia and Thailand. Indonesian education is part of cultural sovereignty, not just political sovereignty. The birth of the education system in Indonesia came from the grassroots of society. The education sector needs to be improved in terms of the system, actors including teachers and students, as well as cultivating tolerance in the classroom with various educational policies. Education now makes measuring human abilities the main and most important indicator. However, it is impossible for education to measure human abilities to limit, reduce and ultimately hide human abilities from themselves because humans have diversity. 262 million people are expected to be university students worldwide by 2025. The government is an institution that has the authority to make and take decisions in the form of policies regarding education. Policies regarding education depend on the problems that occur. The current problem is differences in understanding and thinking about diversity. Diversity includes cultural values that exist in society. Cultural values come from the place of residence and society, which is local wisdom which is the basis of multicultural education. Keyword: Sustainable Development, Policy, Multicultural Education, Primary Schools